Designing social equality architecture, aesthetics, and the perception of democracy - Gage, Mark Foster (New York, New York Routledge, 2019)
"In Designing Social Equality, Mark Foster Gage proposes a dramatic realignment between aesthetic thought, politics, social equality, and the design of our physical world. By reconsidering historic concepts from aesthetic philosophy and weaving them with emerging intellectual positions from a variety of disciplines, he sets out to design a more encompassing social theory for how humanity perceives its very reality, and how it might begin to more justly define that reality through new ways of reconsidering the built environment."--
The aesthetic turn-- The politics of the unknown-- Aesthetic distances defined-- From the critical to the speculative-- Axiomatic equality--
Hierarchy and the problem of the privleged observer--
Race, gender and the politics of omission--
Philosophy and the aesthetics of social engagement--
The equity of equidistance--
Strangely equal--
The invitation of curiosity--
From sustainability to dark ecology--
Revising practice and pedagogy--
The death of disciplinarity--
Beyond prattle--
Includes bibliographical references and index
Keywords: Architecture and society; Equality